Slipping out of reach? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Agricultural and biological journals are becoming even more expensive. A survey by the Agriculture and Life Science College of Cornell University in New York, USA, showed that prices of key publications rose by an average of two-thirds over the...